2020
DOI: 10.7185/geochemlet.2021
|View full text |Cite
|
Sign up to set email alerts
|

Clumped isotope temperature calibration for calcite: Bridging theory and experimentation

Abstract: Clumped isotopes (Δ 47) analysis in carbonates is becoming widespread across the geochemical community as a geothermometer that also allows for the reconstruction of the precipitating fluid δ 18 O composition. While initial Δ 47-temperature relationship discrepancies between laboratories have been considerably reduced over the past 10 years, theoretical temperature calibration and laboratory experimental efforts have still not converged to common ground. Moreover, a lack of high temperature anchor points has w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 38 publications
5
55
0
Order By: Relevance
“…However, this calibration has an unequal distribution of samples in 1/ T 2 space, is anchored at the coldest temperatures by unusual carbonates, and does not contain marine carbonates, which are of particular interest to the clumped isotope community. To address these weaknesses, we combine data from this study with four other carbonate‐standardized calibrations (Jautzy et al., 2020; Meinicke et al., 2020; Peral et al., 2018; cave samples from Breitenbach et al., 2018) to present a composite 1/ T 2 ‐Δ 47 regression that has smaller temperature gaps, is anchored at low temperatures by a variety of samples, and extends the calibration to biogenic marine carbonates: Δ47false(ICDES90°Cfalse)=0.0391±0.0004×106T2+0.154±0.0040.3333em0em0emfalse(r2=0.97false) …”
Section: Resultsmentioning
confidence: 99%
“…However, this calibration has an unequal distribution of samples in 1/ T 2 space, is anchored at the coldest temperatures by unusual carbonates, and does not contain marine carbonates, which are of particular interest to the clumped isotope community. To address these weaknesses, we combine data from this study with four other carbonate‐standardized calibrations (Jautzy et al., 2020; Meinicke et al., 2020; Peral et al., 2018; cave samples from Breitenbach et al., 2018) to present a composite 1/ T 2 ‐Δ 47 regression that has smaller temperature gaps, is anchored at low temperatures by a variety of samples, and extends the calibration to biogenic marine carbonates: Δ47false(ICDES90°Cfalse)=0.0391±0.0004×106T2+0.154±0.0040.3333em0em0emfalse(r2=0.97false) …”
Section: Resultsmentioning
confidence: 99%
“…Several empirical and experimental equations were published in the last decade, providing slightly different Δ 47 -temperature relationships for biogenic carbonates [ 5 ], travertines [ 6 ], and experimental carbonates (e.g., [ 7 9 ]). Following the approach by Coplen [ 10 ], who suggested that the extremely slowly depositing calcite of the Devils Hole (Nevada, USA) may represent true calcite-water equilibrium in a natural environment, a recent study by Daëron et al [ 11 ] offered equations for “equilibrium” temperature dependence of clumped isotope composition and calcite-water oxygen isotope fractionation, based on data gathered for the Devils Hole calcite and a similarly slowly precipitating carbonate deposit formed in the Corchia Cave (Italy).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the Devils Hole and Corchia Cave deposits [ 11 ], stalagmites, the most frequently studied speleothems, generally yield Δ 47 data that significantly deviate from the “equilibrium” values, due to kinetic processes [ 13 , 14 ]. Flowstones, however, are similar to the travertine formations that yield close-to-“equilibrium” Δ 47 data [ 6 , 9 ]. As a result, a pilot study was begun on speleothems in the Baradla Cave (NE Hungary), where stalagmites and flowstones have been researched [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that this method achieves the ideal compromise between eliminating bias and retaining high reproducibility while keeping SST and δ 18 Osw reconstructions independent of the δ 18 Oc values on which the age model is based 20 (see also Supplementary Methods). The clumped isotope temperature calibration by 23 is statistically indistinguishable from the temperature relationship based on theoretical principles within the temperature range discussed in 24 and is the culmination of recent convergence of measurement results between labs across the world and inter-lab standardization efforts 22,49 .…”
Section: Absolute Paleoseasonality Reconstructionsmentioning
confidence: 94%
“…Recent advances in clumped isotope instrumentation and standardization have reconciled previous inter-lab disagreements and shown that many carbonate paleoarchives (e.g. foraminifera, bivalves and eggshells) conform to the theoretical Δ47 temperature calibration 23,24 (see Supplementary Methods and Discussion). The large sample sizes required for individual Δ47-based temperature estimates (>2 mg) have complicated paleoseasonality reconstructions using this accurate method 25 , but a recently developed statistical approach enables its use for seasonality reconstructions 20 .…”
Section: Introductionmentioning
confidence: 92%